Thermostimulated luminescence of SrB₄O₇ single crystals and glasses - Dubovik, M.F.; Korshikova, T.I.; Oseledchik, Yu.S.; Parkhomenko, S.V.; Prosvirnin, A.L.; Svitanko, N.V.; Tolmachev, A.V.; Yavetsky, R.P. (Functional Materials, 2005)
Thermostimulated luminescence (TSL) of X-ray irradiated SrB₄O₇ single crystals and glasses has been studied for the first time and compared with polycrystalline samples. The TSL of SrB₄O₇ single crystals is due to radiative recombination of charge carriers trapped on the intrinsic defects of the crystal lattice. The X-ray luminescence of SrB₄O₇ single crystals peaked at λ ≈ 330 to 340 nm is ascribed to the self-trapped exciton emission. In SrB₄O₇ glasses, the TSL seems to be connected with decomposition of F-like centers and О⁻ ones.